DAMPAK PERUBAHAN ORGANISASI PADA KINERJA PEGAWAI DI BALAI BESAR PERAKITAN DAN MODERNISASI PERTANIAN TANAMAN PADI - Hanimah Putri, Siti; Retnosary, Rieke; Triadinda, Dexi (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
This research is directed to examine in-depth the form of organizational change that occurred at the Rice Agricultural Assembly and Modernization Center (BRMP) and analyze the impact on employee performance through employee experience, perception, and view. Research findings indicate that the organizational change in BRMP Padi is not just a change in the name of the institution, but a complex structural and functional change, from a research-based organization, switching to a standardization orientation, to an organization that combines the functions of technology assembly, modernization, and standardization. Although the quality of performance is relatively maintained, the employee's response to change is adaptive but accompanied by the dynamics of adjustment in the initial phase formed by previous experience of change. The research concludes that the sustainability of employee performance is highly dependent on policy clarity, budget support, human resource adequacy, and the active role of leaders in managing organizational changes. This study contributes to enriching the study of organizational change in the public sector by providing an empirical understanding of the impact of repeated organizational changes on employee performance and the importance of sustainable change management.